Analisis Spasial Sebaran Kejadian Kasus Diare dengan Keberadaan E. Coli Pada Air Sumur Dan Kepadatan Penduduk Di Kalurahan Tirtonirmolo, Kec. Kasihan, Kab. Bantul - Novita Husnul Munawarah; Rizki Amalia; Achmad Husein; Siti Hani Istiqomah (Poltekkes Kemenkes Yogyakarta, 2022)
In 2018, diarrhea in Indonesia was classified as a potential endemic disease of Extraordinary Events which was often accompanied by death. Well water can be a medium for transmitting diarrhea in the community, this transmission can occur because well water is contaminated with E. coli. In addition, population density can be a factor in the occurrence diarrhea. This study aims to determine the spatial analysis of the distribution diarrhea cases with the overlay method, which was carried out by analyzing the distribution pattern using Average Nearest Neighbor and Spatial Autocorrelation Report. Of the 26 scattered cases, the results of spatial analysis related to the presence of E. coli showed that there was a relationship between the incidence of diarrhea cases and the presence of E. coli, whose distribution pattern was clustered. The level of risk the presence of E. coli in well water with other environmental risk factors (wastewater disposal facilities, latrines and garbage disposal) showed that the most points found were those with moderate risk. In addition, the results of spatial analysis distribution diarrhea cases with population density showed that there was no significant relationship between the distribution diarrhea cases and population density, the distribution pattern was random.